A Review of the Impact and Challenges of Hikmah Pedagogy in Teaching and Learning Environment (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
Implementing an effective pedagogy that can enhance students' critical thinking, reasoning abilities, decision-making skills, and problem-solving capabilities is a key educational objective in the 21st century. This necessitates a shift from rote learning to interactive and meaningful learning experiences. Hikmah pedagogy, derived from Philosophy for Children (P4C), is an innovative approach that equips students with the essential skills for thinking, creativity, collaboration, communication, and caring, all while incorporating Islamic values through the Community of Inquiry (CoI) framework. Hikmah pedagogy adopts an infusion approach, fostering curiosity and promoting qualities such as critical thinking, open-mindedness, tolerance, and respect for others when exploring diverse perspectives. Research has demonstrated that the implementation of Hikmah pedagogy positively impacts teaching and learning across various subjects and educational levels. Hence, this review aims to assess the effects of Hikmah pedagogy on teaching and learning, as well as the challenges associated with its implementation. A total of 18 peer-reviewed articles were purposefully selected and analyzed using systematic content analysis (SLR). The findings indicate that Hikmah pedagogy enhances students' higher-order thinking skills (HOTs), critical thinking and reasoning abilities, open-mindedness, and communication skills. Additionally, the review highlights the importance of interactive stimuli, inquiry-based classroom management, and student engagement within the community of inquiry. Based on this evidence, educators are encouraged to incorporate Hikmah pedagogy as an effective teaching tool to cultivate students' thinking skills and moral development.